Strategi Resource-Based dan Inovasi dengan Pendekatan Biaya Daur Hidup Produk untuk Mencapai Keunggulan Daya Saing - Whedy Prasetyo (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
Product development and competition continuously growing in markets to meet consumer needs as consumer, and the goal to achieve cost accuracy and effectiveness during product manufacturing process based on resource strength and weaknesses provide effort in developing internal resource capability of Small and Medium Enterprises (SME) manufacture through application of resource-based strategy (consisting of financial, physical, human and technology resources) and innovation (consisting of product innovation and internal resource) using product life cycle cost approach in achieving competitive advantage. This research suggests that 108 assisted-partner SME manufactures in East Java, using multiple regression analysis provide result in which jointly implementing resource-based strategy and innovation will achieve product competitive advantage. In term of its contribution of the resources, however, there are only three resources, physical resource, product innovation and internal resource, which highly contribute to improve product competitive advantage.Keywords : SME manufacture, resource-based strategy, innovation, product life cycle cost, and product competitive advantage.